A posteriori probabilistic feasibility guarantees for Nash equilibria in uncertain multi-agent games⁎Research was supported by the UK Engineering and Physical Sciences Research Council (EPSRC) under grant agreement EP/P03277X/1. Issue 2 (2020) - Pantazis, George; Fele, Filiberto; Margellos, Kostas
Abstract: In this paper a distribution-free methodology is presented for providing robustness guarantees for Nash equilibria (NE) of multi-agent games. Leveraging recent a posteriori developments of the scenario approach, we provide probabilistic guarantees for feasibility problems with polytopic constraints. This result is then used in the context of multi-agent games, allowing to provide robustness certificates for constraint violation of any NE of a given game. Our guarantees can be used alongside any NE seeking algorithm. Finally, by exploiting the structure of our problem, we circumvent the need of employing computationally prohibitive algorithms to find an irreducible support subsample, a concept at the core of the scenario approach. Our theoretical results are accompanied by simulation studies that investigate the robustness of the solutions of two different problems, namely, a 2-dimensional feasibility problem and an electric vehicle (EV) charging control problem.